Innovations, nudging interventions and food and nutrition security: evidence from experimental and quasi-experimental studies in Ethiopia - Jada, Kaleb Shiferaw (Wageningen University & Research, 2022)
For the majority of developing nations, malnutrition is a recurring issue. Globally, one in ten people are undernourished and though the problem exists in every country, not surprisingly, the extent is more severe in low-income countries. In this part of the world, smallholders play a key role in the food system as they produce diverse and culturally appropriate food. This has an implication for efforts to combat hunger. Efforts that aim to address the problem of malnutrition in the global south should make smallholders its central focus. The current food system contributes to malnutrition and significantly raises global greenhouse gas emissions. This trade-off should be considered while redesigning the food systems to tackle food insecurity and malnutrition. Thus, the challenge is how to alleviate malnutrition in developing countries without putting more strain on the environment or failing to protect smallholders.